2014
DOI: 10.1111/jphp.12298
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor β-mediated site-specific Smad linker region phosphorylation in vascular endothelial cells

Abstract: TGF-β-mediated phosphorylation of individual serine/threonine sites in the linker region of Smad2 occurs in a highly specific manner by kinases. These phosphorylations provide an opportunity to further understand a therapeutically targeted and very specific signalling pathway in vascular endothelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…In vascular endothelial cells, Smad2 linker region residues are phosphorylated by different serine/threonine kinases that alter plasminogen-activator inhibitor 1 mRNA expression (Kamato et al, 2014). Here we used two antibodies, with one detecting the cluster of serine residues (Ser245/250/255) and the second, the phosphorylated threonine residue (Thr220).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vascular endothelial cells, Smad2 linker region residues are phosphorylated by different serine/threonine kinases that alter plasminogen-activator inhibitor 1 mRNA expression (Kamato et al, 2014). Here we used two antibodies, with one detecting the cluster of serine residues (Ser245/250/255) and the second, the phosphorylated threonine residue (Thr220).…”
Section: Discussionmentioning
confidence: 99%
“…Site-specific antibody for phospho-Thr220 was used to investigate the involvement of the Thr220 residue (Matsuzaki et al, 2009;Kamato et al, 2014). We have previously reported that TGF-β treatment stimulates the phosphorylation of Thr220 with a peak response at 1 h (Rostam et al, 2016).…”
Section: Flavopiridol Effects On Tgf-β-stimulated Biglycan Synthesis mentioning
confidence: 99%
“…[S/T]-P phosphorylation of SMADs by multiple kinases, including the JNKs (326,327), switches their interactions with YAP/TAZ transcription factor proteins toward binding to the NEDD4-like E3 ubiquitin ligase Smurf1 (328). In this example, one of the multiple WW domains of Smurf1 mediating this interaction requires the canonical PPxY motif, but the other recognizes phosphorylated motifs instead and it binds in a reverse orientation, thus promoting interaction and the subsequent degradation of SMAD1 (328).…”
Section: Jnk Phospho-switches Potentiating New Protein-protein Bindinmentioning
confidence: 99%
“…Reports by Chung et al (Chung et al 2013) demonstrate PAR-2 transactivation of TGFBR1 in their renal fibrosis model to have identical mechanisms to that occurring in our VSMCs model ) with the exception that MMPs are involved in the phosphorylation of Smad. The phosphorylation of Smad in the carboxy terminal is a direct result of the kinase activity of TGFBR1 directed to Smad2 or Smad3 (Kamato et al 2013(Kamato et al , 2014, however Smad transcription factors are also phosphorylated in the linkage region this response is not direct but is mediated via serine/threonine kinases (Kamato et al 2013). To expand on the role of MMPs in GPCRs mediated transactivation dependent signalling we used antibodies to both the phosphorylated Smad2 carboxy terminals and linker region (Kamato et al 2016a).…”
Section: Gpcr Transactivation Of Protein Serine/threonine Receptorsmentioning
confidence: 99%